Impact of water content and dietary organic carbon richness on gut bacteria in the earthworm Lumbricus terrestris. Issue 1 (9th October 2020) - Zeibich, Lydia; Guhl, Jennifer; Drake, Harold L
ABSTRACT: Many higher and lower animal gut ecosystems have complex resident microbial communities. In contrast, ingested soil is the primary source of the gut microbial diversity of earthworms, invertebrates of fundamental importance to the terrestrial biosphere. Earthworms also harbor a few endemic bacteria including Tenericutes -affiliated Candidatus Lumbricincola of unknown function. Gut microbes are subject to nutrient fluctuations due to dilution effects during gut passage, the nutrient richness of the anoxic gut, and dietary organic carbon, factors that could alter their activity/detection. This study's objective was to assess the potential impact of these factors on the occurrence and activity of ingested and endemic bacteria in gut content of Lumbricus terrestris . Fermentation product profiles of anoxic undiluted and diluted gut content treatments were similar, suggesting that experimental increase in water content and nutrient dilution had marginal impact on fermentation. However, 16S ribosomal Ribonucleic Acid (16S rRNA) sequence abundances indicated that stimulated bacterial taxa were not identical in undiluted and diluted treatments, with dominate potentially functionally redundant phylotypes being affiliated to the Firmicutes, Fusobacteria and Proteobacteria . Although the earthworm-associated Tenericutes were not stimulated in these treatments, the occurrence of three Tenericutes -affiliated phylotypes varied with the organic carbon richness of the earthworm diet, with two phylotypes being associated with high organic carbon richness. 16S rRNA sequence abundances indicated that other dominant gut taxa also varied with dietary organic carbon richness. These findings illustrate that functionally redundant ingested bacteria and earthworm-associated Tenericutes might be influenced by nutrient fluctuations in the gut and organic carbon richness of the earthworm diet. Abstract : Earthworms are fundamental subsurface invertebrates, and this study illustrates that ingested bacteria and earthworm-associated Tenericutes might be influenced by nutrient fluctuations and dietary organic carbon richness.